2008
DOI: 10.1103/physrevb.77.205438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen passivation on luminescence-center-mediated Er excitation in Si-richSiO2with and without Si nanocrystals

Abstract: The influence of hydrogen passivation on luminescence-center-mediated excitation of Er 3+ in Er-doped Si-rich SiO 2 films with significantly different microstructures is studied. Photoluminescence measurements are presented for samples containing no detectable silicon nanocrystals ͑annealed at 600°C͒ and for samples containing silicon nanocrystals ͑annealed at 1100°C͒ as a function of hydrogen passivation temperature. Passivation is found to have little effect on the Er 3+ photoluminescence intensity at 1535 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 65 publications
(111 reference statements)
1
26
0
Order By: Relevance
“…3,25 The slight shift to higher energies, in spite of T d increase, reflects some lowering in the average size of Si-nc which is quite compatible with the above-commented decrease in Si excess. It is also worth noting that this visible emission was similarly observed and attributed to Si-nc by Savchyn et al 9,26,27 for their samples annealed at 1000°C during only 100 s. On the contrary, no contribution is detected in our samples of the so-called luminescent centers ͑LCs͒ emitting at around 500 nm. 9 The presence of a significant Er-PL in our as-deposited samples ͑for T d Ն 200°C͒ excited with a nonresonant wavelength reveals the occurrence of an efficient energy transfer from Si-nc to Er 3+ .…”
Section: A Structural Analysesmentioning
confidence: 46%
“…3,25 The slight shift to higher energies, in spite of T d increase, reflects some lowering in the average size of Si-nc which is quite compatible with the above-commented decrease in Si excess. It is also worth noting that this visible emission was similarly observed and attributed to Si-nc by Savchyn et al 9,26,27 for their samples annealed at 1000°C during only 100 s. On the contrary, no contribution is detected in our samples of the so-called luminescent centers ͑LCs͒ emitting at around 500 nm. 9 The presence of a significant Er-PL in our as-deposited samples ͑for T d Ն 200°C͒ excited with a nonresonant wavelength reveals the occurrence of an efficient energy transfer from Si-nc to Er 3+ .…”
Section: A Structural Analysesmentioning
confidence: 46%
“…The samples annealed by the RTP only are referred to as "as-annealed" samples and the samples annealed by the RTP and passivated are referred to as "passivated" samples. The purpose of the passivation is to remove the dangling bond defects surrounding Si nanostructures (Savchyn et al, 2008;Wilkinson & Elliman, 2003). In our study, we have varied the passivation time and found that after 30 minutes of the passivation, the emission intensity of exciton recombinations in Si nanocrystals as well as the exciton lifetime have reached the optimum values and saturated, showing that most, if not all, dangling bond defects have been effectively removed.…”
Section: Preparation Of Si Nanostructures Embedded In Sio 2 Matrix Wimentioning
confidence: 99%
“…Prior to 2007, many research works reported that the main energy transfer mechanism is from Si nanocrystals to Er 3+ ions (Fujii et al, 2004;Heitmann et al, 2003;Kik & Polman, 2001;Polman & Veggel, 2004). However, recently, in 2007 and2008, one leading group in the field suggested that defect mediated energy transfer was the dominant mechanism (Savchyn et al, 2007(Savchyn et al, , 2008. In their work (Savchyn et al, 2007(Savchyn et al, , 2008, the origin of defects that transfer energy to Er 3+ ions was not discussed.…”
Section: T O O V E R C O M E T H I S P R O B L E M E R B I U M ( E mentioning
confidence: 99%
See 2 more Smart Citations